Studi Literatur Bakteri Asam Laktat Yang Diisolasi Dari Susu Kuda, Susu Kambing Dan Susu Sapi - Surak, Andianus Fransiskus; Ndaong, Nemay A; Detha, Annytha I.R (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
The purpose of this study is to know the dominant type, with characteristics and benefits of lactic acid bacteria that are isolated from horse milk, goat milk and cow's milk. The method used is a qualitative descriptive method with a literature study approach. Based on the results of studies obtained lactic acid bacteria consist of several genera, namely Lactobacillus, Streptococcus, Leuconostoc, Enterococcus, Lactococcus, Tetragenococcus and Pediococcus. Lactobacillus is the dominant species in the milk of horses and goat's milk, whereas in cow's milk the dominant species is Lactobacillus and Pediococcus. Based on nature and morphology, lactic acid bacteria is a group of positive, coccus or rod-shaped bacteria, non-spore forming bacteria, and able to ferment glucose to produce lactic acid. Lactic acid bacteria are anaerobic, not motil, negative catalyst, positive oxidase, growth optimium temperature ± 40 °C and pH 4-5. Lactic acid bacteria can provide a positive effect for health by manging intestinal mokroflora, reducing pathogenic bacteria and stimulating immune responses to lower the risk of disease.